2018
DOI: 10.1002/cnma.201700391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Reinforcement of Graphene Sheets into Alkyd Resin Matrix for the Development of Electrically Conductive Paints

Abstract: In this work, we are reporting the preparation of graphene‐based conductive paints using mechanochemically prepared graphene nanosheets as a conductive pigment and alkyd resin as the binder with non‐toxic additives. The surface morphology and intermolecular interactions between the graphene pigments and alkyd resin in the prepared graphene nanopaint are studied using field emission scanning electron microscope, X‐ray photoelectron spectroscopy, and Raman spectroscopic analysis, respectively. The formation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Figure 8 shows the infrared spectra of the thermochromic coating with different contents of microcapsules. The coating without the microcapsules had a telescopic peak of the hydroxyl group at 3445 cm −1 , a characteristic peak of C=O in ester bond at 1730 cm −1 , and a characteristic peak of C-H in the methyl and methylene groups at 2929 cm −1 and 2849 cm −1 , which are characteristic peaks of alkyd resin coating [ 53 ]. The telescopic peak of the N-H bond and the O-H bond was 3353 cm −1 , 2957 cm −1 was the asymmetric stretching vibration of -CH 2 -, 1637 cm −1 was the carbonyl telescopic peak of secondary acyl, and 1131 cm −1 was the characteristic absorption peak of CH 3 O.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 shows the infrared spectra of the thermochromic coating with different contents of microcapsules. The coating without the microcapsules had a telescopic peak of the hydroxyl group at 3445 cm −1 , a characteristic peak of C=O in ester bond at 1730 cm −1 , and a characteristic peak of C-H in the methyl and methylene groups at 2929 cm −1 and 2849 cm −1 , which are characteristic peaks of alkyd resin coating [ 53 ]. The telescopic peak of the N-H bond and the O-H bond was 3353 cm −1 , 2957 cm −1 was the asymmetric stretching vibration of -CH 2 -, 1637 cm −1 was the carbonyl telescopic peak of secondary acyl, and 1131 cm −1 was the characteristic absorption peak of CH 3 O.…”
Section: Resultsmentioning
confidence: 99%
“…Another study also concluded that preparation of titanium oxide (TiO2) nanopaint by embedding the TiO2 nanoparticles in alkyd resin matrix exhibited substantially enhanced antibacterial properties against a wide range of different types of bacterial strains [118]. Others also reported similar findings of enhanced corrosion-resistant behavior and anti-bacterial properties of nanoformulated paints [119][120][121][122][123][124]. Clearly, results from various studies demonstrate that these new coating formulation of nanopaint to be of tremendous value to researchers and industry.…”
Section: Nanoparticle and Cementmentioning
confidence: 94%
“…Through the ball‐milling technology, GO can be subjected to various types of mechanical forces, such as impact, shear, friction, compression, and grinding caused by phenomena like intense collision, friction, and impact from the grinding tank, grinding ball, powder, and grinding additives. These processes would accumulate the mechanical energy, promote changes in organization and structure, enhance the surface activity and reactivity of GO, induce and accelerate system chemical cross‐linking reactions, enhance the grafting rate of GO onto high molecular polymers, and increase compatibility between components to finally realize the surface modification of GO 28–30 . However, research dealing with enhancing the stability of GO‐containing slurries via ball‐milling technology is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These processes would accumulate the mechanical energy, promote changes in organization and structure, enhance the surface activity and reactivity of GO, induce and accelerate system chemical cross-linking reactions, enhance the grafting rate of GO onto high molecular polymers, and increase compatibility between components to finally realize the surface modification of GO. [28][29][30] However, research dealing with enhancing the stability of GO-containing slurries via ball-milling technology is still lacking.…”
Section: Introductionmentioning
confidence: 99%